System principles of implementation the effective social and environmental monitoring in Ukraine - Nagorniuk, Oksana; Ridei, Nataliia; She, Olga; Bogucki, Yuriy (Wydawnictwo Uniwersytetu Rzeszowskiego, 2016)
The analysis of the basic principles of environmental monitoring and executive functions authorities of environmental monitoring system was made. The method of improvement the ecological environment monitoring by means of social and environmental monitoring was proposed.
Keywords: environmental monitoring; system principles of environmental monitoring; performers of environmental monitoring; social and environmental monitoring; ecological safety